Perancangan Kemasan Makanan Pesan-Antar Berdasarkan Perspektif Konsumen - Maya Setiawardani; Harmon harmon; Mukaram Mukaram; Ira Siti Sarah; Ermina Tiorida; Mohammad Rizal Gaffar; Iwan Mulyawan (Politeknik Negeri Batam, 2021)
In recent years, the market for delivery foods has grown rapidly. The large-scale social restrictions that were announced by Indonesian government as a response to Covid-19 pandemic has continued the increasing trend of online food delivery. Convenient and health factors are the main motivator of this trend. Therefore, there is a growing concern about the effective packaging design for takeout foods. However, only a few a study published on this specific topic. It is important to understand the main concern of customers on the takeout foods packaging design. The purpose of this study is to design suitable takeout foods packaging based on the customer perspective using a pull market strategy. This study used various data collection methods such as observation, interview, literature study, and survey. Data collected was analyzed with descriptive analysis and SWOT analysis. A packaging design is proposed considering customer inputs on packaging material, design, and information needed.